2010
DOI: 10.1192/bjp.bp.109.075317
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of obsessive–compulsive disorder: follow-up of 142 children and adolescents

Abstract: This study confirms that paediatric OCD can be a chronic condition that persists into adulthood. Early recognition and treatment might prevent chronicity. Important challenges for services are ensuring adequate treatment and a smooth transition from child to adult services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
93
1
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(104 citation statements)
references
References 27 publications
4
93
1
6
Order By: Relevance
“…Focusing on the studies that have used non-clinical samples, the remission rate is even higher, at 74%. Some more recent studies from the USA 97,98 and the UK 99 have also been published. The results of more recent studies are similar to those seen in the Stewart et al review, 96 despite the use of selected samples from tertiary centres.…”
Section: Natural History: Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…Focusing on the studies that have used non-clinical samples, the remission rate is even higher, at 74%. Some more recent studies from the USA 97,98 and the UK 99 have also been published. The results of more recent studies are similar to those seen in the Stewart et al review, 96 despite the use of selected samples from tertiary centres.…”
Section: Natural History: Prognosismentioning
confidence: 99%
“…In the Yale cohort, 98 58% of the patients had complete remission after a mean follow-up duration of 9 years. In the Maudsley cohort, 99 approximately 60% of the patients had at least a partial remission after 5 years' mean follow-up. From these findings it can be concluded that remission rates in children and adolescents may be higher than those in adults.…”
Section: Natural History: Prognosismentioning
confidence: 99%
“…Quality of life is seriously impaired in OCD, more so than, for instance, in depression (Srivastava et al, 2011). Various longitudinal clinical studies have established that in contrast to children/adolescents in whom OC symptoms seem to remit somewhat more often (Fernández de la Cruz et al, 2013;Leckman et al, 2009;Micali et al, 2010;Stewart et al, 2004), in adults, OC symptoms tend to be more stable with respect to symptom dimensions, with probability estimates of full remission between 17% and 27%, and of partial remission of between 22% and 53% in the course of up to 40 years, depending on study methodology (prospective vs. retrospective), and country of origin (Alonso et al, 2001;Eisen et al, 2013;Mancebo et al, 2014;Orloff et al, 1994;Reddy et al, 2005;Skoog & Skoog, 1999;Steketee et al, 1999). Specifically, in patients who only experience partial treatment response, symptoms recur in up to 70% of patients within 5 years of follow-up (Eisen et al, 2013).…”
mentioning
confidence: 99%
“…Obsessions and compulsions are behaviors that do not feel consistent with the patient's own beliefs about what is reasonable. For a long time, the disorder was thought to be rare in children and adolescents, but we now know that OCD often starts in childhood and adolescence and can develop into a chronic disorder with high rates of persistence [7]. The prevalence of OCD in childhood and adolescence is reported to be between 0,5% and 4% [8][9][10].…”
Section: Introductionmentioning
confidence: 99%